Building a Value-Based Workforce Through Islamic Work Value-Based Recruitment: A Conceptual Review - Mastura Ab. Wahab (Asian Academy of Management Journal, 2024)
The increasing ethical infringements, moral violations, and disciplinary problems among employees point to the deteriorations in employee values. Hiring employees merely on common competency-based recruitment (CBR) versus value-based recruitment (VBR) ignores the critical role of values in guiding employee behaviours, thus contributing further to the problems. This study involves a qualitative approach using NVivo text analysis tool to analyse texts and word frequency from 44 references, including 35 journal articles, six policy papers, two books or book chapters and one conference proceedings. The results show that Public Sector ICT Management Review was the top journal with the highest coverage of the study’s main themes, followed by the Journal of Education for Teaching, the Human Resource Management Review, and the Advances in Health Science Education indicating the importance of the value-based workforce in these four areas of employment (i.e., public sector, education, human resource, and health). The word frequency analysis also shows the five most-used words were “values,” “work,” “based,” “selection,” and “recruitment.” These findings show that the references used in this study are valid and reliable relevant to the study’s main themes. Value-based workforce relates to value-based recruitment – building a value-based workforce begins with a good recruitment strategy. In the Islamic context, Islamic work values are highly influential and Islamic work-related values have been used as recruitment conditions for hiring employees during the Prophet Muhammad’s (pbuh) time and the rightly guided caliphs. If incorporated into the value- based model of recruitment, Islamic-related work values could potentially build a value- based workforce. This study has a significant implication to managers especially in finding good employees for the success of the organisation. Recruiting employees through value-based recruitment and selection is believed could reduce many work-related issues and improve organisational effectiveness. This study adds to the body of knowledge on value- based hiring by incorporating theories and Islamic work ideals, which can be used as a guide for future research.